Molecular dynamics simulation: effect of sulfation on the structure of curdlan triple helix in aqueous solution - Gao, Yufu (2025)
In this work, by using molecular dynamics simulations, we elucidate the effect of sulfation substitution on the stability of the curdlan triple helix structure. The simulation results indicate that the stability of the triple helix structure is significantly influenced by the sites of sulfation substitution. The substitution at the O2 site directly disrupts the hydrogen bonding network between the triple helix chains, significantly destroying the triple helix conformation. When substitutions occur at both the O4 and O6 sites simultaneously (O4,6), the electrostatic repulsion between numerous sulfate groups introduces considerable energy perturbation to the triple helix, leading to alterations in the glucan chain conformation and consequent destabilization of the triple helix structure. Meanwhile, we find that even if the sulfation substitution is performed at the same substitution sites, the difference in the degree of substitution also has an impact on the triple helix stability. The resistance of the triple helix to sulfation substitution at O2 is weak, and low degree of substitution can lead to the unwinding of the triple helix. However, it demonstrates higher resistance to substitution at O4,6 where only higher degree of substitution results in triple helix destabilization.